USING POWER STRATEGY ON STUDENTS’ DESCRIPTIVE TEXT WRITING ABILITY: IT’S EFFECTIVENESS - Rambe, Siti Rahma; Daulay, Sholihatul Hamidah; Ramadhan, Achmad (Faculty of Tarbiyah nad Teacher Training, 2024)
This study examines how well ninth-grade students at SMP Negeri 1 Rantau Utara use the POWER approach to improve their writing skills in descriptive texts. Because they don't want to learn how to write in English and because the approaches aren't engaging enough, the students' writing skills are poor. This issue needs to be taken into account because students' motivation to write in English will be impacted if they are not interested in learning the language. The study utilized a quasi-experimental design featuring a pre-test/post-test control group structure, as well as quantitative technique. The experimental group received teaching utilizing the POWER technique (Plan, Organize, Write, Edit, Revise), whereas the control group received standard writing instruction. Students from SMP Negeri 1 Rantau Utara's ninth grade made up the research's population. The study included sixty students, divided equally into thirty in the experimental group and thirty in the control group. Data analysis was conducted using the t-test in SPSS version 23, revealing a difference in writing proficiency between the students in the experimental and control groups. Evidence for this is the significance, or Sig. (2-tailed), which was reached 0.000<0,05, indicating the acceptance of Ha and the rejection of H0. According to the results of the aforementioned study, ninth-grade students at SMP Negeri 1 Rantau Utara can enhance their writing skills by utilizing the POWER Strategy.